Features and predictive value of 6-min walk test outcomes in interstitial lung disease: an observation study using wearable monitors - Jiaying Li; Xiaobing Wu; Xiaoyan Li; Miaozhen Deng; Xinyin Liang; Huiqun Wei (BMJ Open)
Objectives To describe 6-min walk test (6MWT) outcomes, and to investigate their correlations with cardiopulmonary and lung function among patients with interstitial lung disease (ILD) which was not limited to idiopathic pulmonary fibrosis.Methods We collected patients’ demographic data and obtained minute-by-minute 6MWT outcomes. Modified Borg scale was employed to assess patients’ dyspnoea, whereas New York Heart Association (NYHA) classification and pulmonary function test were used to evaluate patients’ cardiopulmonary functions.Results Heart rate (HR) exhibited a continuous upward trend, while SpO2 exhibited an overall downward with a slight increase at the fifth minute. The SpO2 nadir for 70 patients (9.3%) was lower than 80%. Further, the SpO2 nadir for 78.27% of the participants appeared at the end of the fourth minute. The 6-min walk distance (6MWD) had the strongest correlation with NYHA classification (r=0.82, p<0.01). The ratio of 6MWD to predicted 6MWD was most correlated to forced expiratory volume in the first second (r=0.30, p<0.01) and forced vital capacity (r=0.30, p<0.01). SpO2 at 3 min had the strongest correlation to patients’ diffusing capacity of the lungs for carbon monoxide (r=0.41, p<0.01). We found significant differences in 6MWD (F=2.44, p=0.033), SpO2 change (F=2.58, p=0.025), HR at 0 min (F=2.87, p=0.014), HR at end of 6 min (F=2.58, p=0.025) and HR zenith (F=2.64, p=0.022) between the subtypes of ILD.Conclusion This observation provided an important evidence regarding oxygen titration. It is better to maintain SpO2 above 88% for 4 min instead of 3 min. SpO2 at the third minute was the most valuable predictor of patients’ lung function. 6MWD and SpO2 changes were more discriminative in subtypes.